Clinical and Biochemical Characteristics of Severe Hypothyroidism Due to Autoimmune Thyroiditis in Children - Kucharska, Anna Małgorzata; Witkowska-Sȩdek, Ewelina; Labochka, Dominika; Rumińska, Małgorzata (Frontiers in Endocrinology, 2020)
In the majority of countries autoimmune thyroiditis is the main cause of acquired hypothyroidism in children. Typically the natural course of disease is initially insidious and diagnosis is incidental. Simultaneously, there are some children who develop severe hypothyroidism without a proper diagnosis. The aim of the study was to analyze clinical and biochemical profile of children with severe primary hypothyroidism due to autoimmune thyroiditis. Materials and methods: We analyzed the records of 354 patients diagnosed between 2009 and 2019 with autoimmune thyroiditis. Only patients with TSH above 100 µIU/mL associated with decreased free thyroxine and the presence of antithyroid antibodies were enrolled to the study. The analysis encompassed clinical symptoms, thyroid and biochemical status, bone age and imaging. Results: 26 children were enrolled to the study. The mean age at diagnosis was 10.26 ± 3.3 years, female preponderance 1.8:1. The most frequent symptom was growth impairment (77%) and weight gain (58%). Goiter was present in 42% of patients. The less common finding was pituitary hypertrophy (4 patients) and hypertrichosis (3 patients). Median values at the time of diagnosis were: TSH 454.3 uIU/ml (295.0– 879.4), anti-TPO antibodies 1090 IU/ml, anti-Tg antibodies 195 IU/ml. Anti-TSHR ab were evaluated only in 6 out of the 26 patients. Characteristic biochemical profile was correlated with the grade of hypothyroidism and the strongest correlations were found with CBC parameters, lipid profile, aminotransferases and creatine. Conclusion: In children with severe hypothyroidism, the most sensitive symptoms are growth arrest and weight gain despite the fact that in some children the auxological parameters at presentation could be within normal values for the population. The specific biochemical profile is closely correlated with severity of thyroid hormones deficiency and involves mostly erythropoiesis, liver and kidney function. Pituitary enlargement should be considered in each child with severe hypothyroidism. It is necessary to conduct prospective studies evaluating the actual frequency of anti-TSHR antibodies and pituitary enlargement in children with extremely high TSH, especially without goiter.